(untitled) (Global Journal of Science Frontier Research, 2014)
In the digital space structure, space is digitalized by 1 and 0 for attachment space and detachment space, respectively. A special force field (the short-range extreme force field) can be derived from the digital space structure to generate superconductor at extremely low temperature and superstar at extremely high density. Singularity-free superstar is a model for the collapse of large stars and for GRBs, and as an alternative to black hole. Attachment space allows object to attach to account for rest mass and reversible movement, while detachment space allows no object to attach to account for irreversible kinetic energy. The combination of attachment space and detachment space brings about the three structures: binary partition space, miscible space, orbinary lattice space. Binary partition space (1) n (0) n consists of separated continuous phases of attachment space and detachment space to account for quantum mechanics and extreme force field. In miscible space (1+0) n , attachment space is miscible to detachment space without separation to account for special relativity.